PROPOSAL OF A METHODOLOGY FOR THE IMPLEMENTATION OF INVESTMENT PROJECTS IN CHEMICAL PROCESS PLANTS - Gómez Franco, María Lidia; Valdés Balmaseda, Claudia; Bonachea Crespo, Mijail (Centro Azúcar Journal, 2026)
Introduction: Capital investment projects in the Cuban industrial sector face difficulties because they are not executed with the required level of quality. Objective: To develop a methodology for implementing investment projects in process plants that ensures the achievement of planned outcomes throughout all stages: conception, execution, start-up, and subsequent operation. Materials and Methods: A systematized method was formulated by integrating two documented methodologies for the implementation of investment projects. This method encompasses a detailed set of stages outlining how investments should be managed, specifying its application in the chemical industry. Results and Discussion: The fundamental indicators of a capital project are evaluated, highlighting the indispensability of these aspects and incorporating maintenance as a core element of the investment process in Cuban industry, particularly in the chemical sector. Conclusions: The implemention of this new methodology facilitates a detailed analysis of each aspect and covers all the necessary stages for the advancement of the project.